A Case of 3D Virtual Laboratory Design Implementation and Intelligence for Mechatronics Courses - Li, Yuxin; Liang, Wei; Jia, Hang; Jian, Hongyu; Zhao, Xin (Innovative Applications of AI, 2025)
Laboratory courses play a pivotal role in higher education, and with emerging technologies transforming instructional practices, virtual laboratories have become an effective supplement to traditional, face-to-face settings. This paper presents a Unity3D-based virtual production line laboratory platform developed under the ADDIE instructional design model (Analysis, Design, Development, Implementation, Evaluation). The physical assembly line was replicated in a virtual environment and deployed via WebGL on a custom website, enabling students to engage in experimental learning at any time.Additionally,On the student client, we have visualised PLC programs and designed an image recognition module that enables students to visually verify the correctness of their PLC programs. Implementation with second-year undergraduates demonstrated positive impacts on academic performance.